Native and engineered defects in transition metal dichalcogenides towards atomic-scale quantum systems - Aliyar, Thasneem (Nanyang Technological University, 2023)
Atomic-scale quantum systems based on individual charges and spins confined to point defects are a promising platform for a range of applications, including quantum computing, communication, sensing, and simulation. Transition metal dichalcogenides (TMDCs), particularly atomically thin semiconductors, are exciting candidates for electronic, optoelectronic, and spintronic applications due to their large and tunable band gap, strong spin-orbit coupling, and inequivalent valleys. Monolayer TMDCs exhibit spin-valley coupling, which provides additional advantages and allows them to serve as spin-valley qubits. In this thesis, I report strongly confined native and engineered atomic-scale defects in MoS2 and substitutionally doped WSe2. We demonstrate resonant tunneling through individual sulphur vacancies in monolayer MoS2, resolving their localized in-gap states and mapping the defect wavefunctions of three distinct charge states. The analysis using orthodox Coulomb blockade theory confirms a large on-site Coulomb charging energy contributing to the splitting of in-gap states of chalcogen vacancies, rather than the spin-orbit coupling. Additionally, we observe asymmetric wave functions associated with V 1−S state, indicating the role of Jahn Teller distortion in splitting between two charge states. Fourier analysis of the sulphur defect wave function confirms that electrons in the sulphur defect site are drawn from the MoS2 Q valleys, rather than the band-minimum at K, also suggesting the presence of inter-valley scattering between Q-Q′ valleys. Furthermore, this thesis provides a detailed atomic-level understanding of magnetic doping in TMDCs, focusing on the influence of in-gap defect states and defect densities on few-layer and monolayer Cr:WSe2. The experimental results confirm that Cr dopants occupy W substitutional sites, resulting in n-type doping. The high concentration of Cr dopants in few-layer Cr:WSe2 shows the formation of impurity bands with extended quasiparticle states showing scattering and interference, confirming inter-valley scattering within these impurity bands between K −K′ points at the Brillouin zone due to the presence of magnetic Cr scatterers. These results may provide new insights into the nature of defect-bound electrons and spins and their potential applications as atomic-scale quantum information carriers.